Determining Attitudinal Beliefs about Controversial Advertising - Ernest Cyril, de Run; Hiram, Ting (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study aims to determine the beliefs about advertising of two controversial products, namely political parties and sexual diseases prevention. The theory of reasoned action was utilized as underlying premise to elicit beliefs about controversial advertising in order to understand the formation of attitude towards the advertising. A qualitative approach by means of personal interview was adopted to explore the relatively unknown phenomenon. Subsequently, 43 interviews were conducted in Sarawak and the transcripts were then content-analyzed by multiple coders. The findings show that there are 11 statements of belief for the advertising of political parties and 6 statements for the advertising of sexual diseases prevention. Although both types of advertising are primarily considered as a source of information, their descriptions are largely different. While the advertising of political parties is mainly believed to be giving misleading information and for personal interest, the advertising of sexual diseases prevention is regarded as a form of education when executed appropriately. Therefore, the former must be carried out with care to avoid negative responses, and the latter should be done fittingly. This articulates the underlying consideration that there are different beliefs by type of advertising, and about what might create controversy.